Nonlinear relationship between body roundness index and prevalence of rheumatoid arthritis in American adults - Cao, Xingze; Tan, Yongtao; Feng, Qiufeng; Ye, Pei; Sun, Hui; Zang, Xuehui (Frontiers in Nutrition, 2025)
BackgroundThe Body Roundness Index (BRI) assesses obesity and fat distribution, yet its correlation with rheumatoid arthritis (RA) is unclear. This study investigated the association between BRI and RA prevalence.MethodsUsing NHANES data from 2011–2018, we conducted a cross-sectional analysis. Logistic regression assessed the BRI-RA relationship, adjusting for various variables. Restricted cubic splines and threshold saturation analysis explored nonlinear associations. Subgroup and sensitivity analyses confirmed the robustness of findings.ResultsA total of 19,875 participants were included in the cross-sectional study. Participants with RA had significantly higher BRI compared with non-RA participants. Logistic regression showed that BRI was positively associated with RA prevalence (OR = 1.14, 95% CI = 1.10–1.17). This positive association remained stable after the inclusion of different covariates (OR = 1.07, 95% CI = 1.02–1.13). Threshold saturation analysis determined a critical BRI value of 5.47, below which the association was strong and above which the association was weakened. Subgroup and sensitivity analyses were consistent with the results of this study.ConclusionIn American adults, higher BRI levels are significantly associated with RA prevalence. Monitoring BRI may help identify individuals at high risk for RA, providing a new perspective on health management.